Study of Working Capital Management on Small and Micro Businesses of Cassava-Based Food in Semarang Regency - Bonifatius Junianto Wibowo; Widuri Kurniasari; Ignatius Supriyanto (JEMAP, 2021)
This research is conducted to know the condition of small and micro business of cassava –based in Semarang regency related to management of working capital.  Samples of this research are ten small and micro business of cassava-based food in that area. That data was obtained with questionnaires, which distributed to those samples. Interview and observation are also used to complete data from questioner. The data are analyzed by descriptive quantitative and quantitative. The result show that they run their business only to get revenue for meeting their basic needs.  While, on the working capital management, they focus on finished goods inventory rather than on raw material inventory.  The easiness of getting the cassava make them have a few  cassava as inventory.   They order cassava from nearest supplier for making any kinds  of food. Most of working capital is financed by owners equity.    Therefore, they do not dependent on creditors.   Nevertheless, they have not yet included wages of workers to create net profit.  Respectively, inventory conversion period, average collection period,  payables deferral period  and cash conversion cycle do not influence to return on asset. In the future, they can take loan to finance working capital as long as not more than owner’s equity.  They should include wages expense to get profit.  More importantly, they must own entrepreneurial spirit in business.